A practical guide to pulsed laser deposition. (14th March 2023) - Shepelin, Nick A.; Tehrani, Zahra P.; Ohannessian, Natacha; Schneider, Christof W.; Pergolesi, Daniele; Lippert, Thomas
Abstract : This tutorial review provides insights on pulsed laser deposition and methods to tune film growth for highly tailored functionalities. Abstract : Nanoscale thin films are widely implemented across a plethora of technological and scientific areas, and form the basis for many advancements that have driven human progress, owing to the high degree of functional tunability based on the chemical composition. Pulsed laser deposition is one of the multiple physical vapour deposition routes to fabricate thin films, employing laser energy to eject material from a target in the form of a plasma. A substrate, commonly a single-crystal oxide, is placed in the path of the plume and acts as a template for the arriving species from the target to coalesce and self-assemble into a thin film. This technique is tremendously useful to produce crystalline films, due to the wide range of atmospheric conditions and the extent of possible chemical complexity of the target. However, this flexibility results in a high degree of complexity, oftentimes requiring rigorous optimisation of the growth parameters to achieve high quality crystalline films with desired composition. In this tutorial review, we aim to reduce the complexity and the barrier to entry for the controlled growth of complex oxides by pulsed laser deposition. We present an overview of the fundamental and practical aspects of pulsed laser deposition, discuss the consequences of tailoring the growth parameters on the thin film properties, and describe in situ monitoring techniques that are useful in gaining a deeper understanding of the properties of the resultant films. Particular emphasis is placed on the general relationships between the growth parameters and the consequent structural, chemical and functional properties of the thin films. In the final section, we discuss the open questions within the field and possible directions to further expand the utility of pulsed laser deposition.